(untitled) (Research, Society and Development, 2023)
In the historical-political-social construction, the intensive care units (ICU) were shaped in places where the technique stands out in relation to aspects related to care, since the working professionals are always emerged by technological devices, which arouses attention for debates about humanized care. In this context, the use of technologies and their implementation in health services should not nullify the health professional’s contact with the patient, as it is visible that interpersonal care is inherent to the practice, essential and complementary to technologies. In addition, light technologies carry out the promotion of humanization in care, affirming the relationships between the professional and the patient, and their insertion in this process strengthens and qualifies the professional’s work process, in the assumptions of autonomy, protagonism and co-responsibility, carrying out transformations in modes of relationship and communication between subjects. Thus, humanization, in health, is linked to ethical issues related to the act of caring for patients, to improve relations between those involved in this process and in working conditions. In the current work, the importance of the correlation between humanization and technology in intensive care units will be addressed. The objective of this study was to analyze the importance of the correlation between humanization and technology in intensive care units, addressing the advantages and disadvantages of computerization in hospital management with a focus on the ICU and ethical issues related to the act of caring for patients, to improve relationships between those involved in this process and working conditions.